Casa tomada - Gascón, Juan Pablo (2024)
Reseña del disco "Casa tomada" de Yasar. 2023. Integrantes: Lucas Yasar, César Diego Altamirano, Federico Alejandro del Río, Morena Pantucci, Juana Olmo, Nehuén Díaz. Producción artística y fonográfica: Yasar.